Variability of Serum Phosphate in Incident Hemodialysis Patients: Association with All-Cause Mortality. Issue 3 (14th March 2023) - ter Meulen, Karlien J.; Ye, Xiaoling; Wang, Yuedong; Usvyat, Len A.; van der Sande, Frank M.; Konings, Constantijn J.; Kotanko, Peter; Kooman, Jeroen P.; Maddux, Franklin W.
Abstract : Abstract : Key Points: An increase in serum phosphate variability is an independent risk factor of mortality. The effects of a positive directional range (DR) is most pronounced in patients with high serum phosphate levels whereas the effects of a negative DR is most pronounced in patients with low serum phosphate and/or serum albumin. Background: In maintenance hemodialysis (HD) patients, previous studies have shown that serum phosphate levels have a bidirectional relation to outcome. Less is known about the relation between temporal dynamics of serum phosphate in relation to outcome. We aimed to further explore the relation between serum phosphate variability and all-cause mortality. Methods: All adult incident HD patients treated in US Fresenius Kidney Care clinics between January 2010 and October 2018 were included. Baseline period was defined as 6 months after initiation of HD and months 7–18 as follow-up period. All-cause mortality was recorded during the follow-up period. The primary metric of variability used was directional range (DR) that is the difference between the largest and smallest values within a time period; DR was positive when the smallest value preceded the largest and negative otherwise. Cox proportional hazards models with spline terms were applied to explore the association between phosphate, DR, and all-cause mortality. In addition, tensor product smoothing splines were computed to further elucidate the interactions of phosphate, DR, and all-cause mortality. Results: We included 302, 613 patients. Baseline phosphate was 5.1±1.2 mg/dl, and mean DR was +0.6±3.3 mg/dl. Across different levels of phosphate, higher levels of DR of phosphate were associated with higher risk of all-cause mortality. In patients with lower levels of phosphate and serum albumin, the effect of a negative DR was most pronounced, whereas in patients with higher phosphate levels, a positive DR was related to increased mortality. Conclusions: Higher variability of serum phosphate is related to mortality at all levels of phosphate, especially in lower levels with a negative DR and in low serum albumin levels. This could possibly reflect dietary intake in patients who are already inflamed or malnourished, where a further reduction in serum phosphate should prompt for nutritional evaluation.